(untitled) (EDUCATION IN THE 21ST CENTURY, 2023)
As the important and fundamental infrastructure for improvement, growth and development and for the achievement of the expected goals of countries, education systems and especially higher education systems need reforms. The article analyzes the current status of higher education in the Bushehr Province, Iran. A study of the various aspects and problems of Iran’s higher education management system can help to modernize its effectiveness, particularly in the Iranian province of Bushehr.